Quality of life and severity of symptoms among patients with various degrees of reflux esophagitis: a prospective study - Amir Mari; Wasef Na’amnih; Loay Ghantous; Helal Said Ahmad; Tawfik Khoury; Khitam Muhsen (Scientific Reports, 2023)
Abstract Gastro-esophageal reflux disease (GERD) can cause erosive esophagitis (EE) and compromise the quality of life (QoL). We examined differences in symptom severity and QoL according to EE severity grade. A follow-up study was conducted among GERD patients at the Nazareth Hospital in Israel. Patients underwent a baseline gastroscopy in 2014–2020 during which the EE grade was determined using the Los Angeles classification. Follow-up telephone interviews were conducted during 2019–2020 with a mean time interval of 18.9 months (SD = 14.9) after the baseline gastroscopy to assess GERD symptoms using the Reflux disease questionnaire (RDQ) and QoL using the GERD QoL questionnaire. The patients were interviewed in their native language (Arabic or Hebrew). Overall, 149 (66.4% males) patients were included; 50 had EE grades C/D and 99 had grades A/B. The mean age at baseline and follow-up was 44.6 years (SD = 15.1) and 46.2 years (SD = 14.9), respectively. Cronbach’s alpha was 0.928 and 0.855 for the RDQ and QoL questionnaires, respectively. Patients with EE C/D grades had more severe symptoms than patients with EE A/B grades (P = 0.05), especially in regurgitation scores (P = 0.03). Females had more severe symptoms (overall) than males (adjusted OR = 2.34; 95% CI 1.12–4.90). Patients with the more severe esophagitis EE C/D group (adjusted OR = 1.98; 95% CI 0.93–4.24) and those who used PPIs treatment (adjusted OR = 2.19; 95% CI 0.95–5.01) reported more severe GERD symptoms. The number of schooling years was significantly associated with better QoL score (beta coefficient 1.33, P = 0.005) but not EE grade or GERD symptoms. Follow-up endoscopy conducted among 22 patients with EE grades C/D showed that 13 (59.1%) of these patients had normal endoscopic findings, 6 patients (27.3%) had a grade A EE, 1 patient (4.5%) had grade B, and 2 (9.1%) remained with grade C EE. The Arabic and Hebrew versions of the RDQ and QoL questionnaires were highly reliable. GERD symptoms severity was more profound among patients with more severe esophagitis. No significant association between EE grade and QoL; this negative result might be due to the improvement in esophagitis endoscopic findings among patients with C/D grade.